2010
DOI: 10.1128/iai.01351-09
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of an Extended Binding Component of the Actin-ADP-Ribosylating C2 Toxin Detected in Clostridium botulinum Strain (C) 2300

Abstract: Clostridium botulinum C2 toxin consists of the binding component C2II and the enzyme component C2I, which ADP-ribosylates G-actin of eukaryotic cells. Trypsin-activated C2II (C2IIa) forms heptamers that mediate cell binding and translocation of C2I from acidic endosomes into the cytosol of target cells. By genome sequencing of C. botulinum strain (C) 2300, we found that C2II from this strain carries a C-terminal extension of 129 amino acids, unlike its homologous counterparts from strains (C) 203U28, (C) 468, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…The cellular uptake of C2 and iota toxins was discovered by us and by others during recent years. C2 toxin consists of the enzyme component C2I (~49 kDa) [31,32] and the binding/translocation component C2II (~80 or 100 kDa, depending on the strain [33,34]). Proteolytically activated C2II forms ring-shaped heptamers (C2IIa) that bind to asparagine-linked carbohydrate structures on mammalian cells [30,33,[35][36][37] and form complexes with C2I.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular uptake of C2 and iota toxins was discovered by us and by others during recent years. C2 toxin consists of the enzyme component C2I (~49 kDa) [31,32] and the binding/translocation component C2II (~80 or 100 kDa, depending on the strain [33,34]). Proteolytically activated C2II forms ring-shaped heptamers (C2IIa) that bind to asparagine-linked carbohydrate structures on mammalian cells [30,33,[35][36][37] and form complexes with C2I.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that secondary structural elements particularly helices and sheets are not altered upon a point mutation, but the loops/coils are reorganized from the native states. Catalytic and binding sites are generally located in the coil and loops of C2 and C3 (Aktories and Barth, 2004;Barth et al, 1998;Kowarsch et al, 2010;Sterthoff et al, 2010). A mutational constraint in those sites may bring conformational flexibility in loop and coils which in turn to decrease in NADbinding affinity and catalytic function.…”
Section: Discussionmentioning
confidence: 99%
“…CDTb was obtained by proteolytic activation of pCDTb (11,34). If not otherwise stated, 1 nM CDTa together with 0.2 nM CDTb were added to cultured cells for intoxication experiments.…”
Section: Methodsmentioning
confidence: 99%